OPINI PUBLIK DI MEDIA SOSIAL TWITTER PADA SOMASI YANG DILAKUKAN OLEH ES TEH INDONESIA - Yogie Alontari; Leti Karmila; Asep Ahmad Siddiq; Neni Yulianita (Jurnal Visi Komunikasi, 2022)
In the current digital era, social media has become a new public space (public sphere) that is used by the public to communicate and interact, including being used to form a public opinion. On September 24, 2022, PT Esteh Indonesia Makmur, as the company that owns the Indonesian Es Tea brand, made a subpoena to the Twitter account owner who criticized one of its beverage products because it was considered a violation of the ITE Law. This became an issue and generated public opinion on social media Twitter. This study intends to find out and analyze the public opinion that is formed from the community of Twitter users towards subpoenas conducted by Es Teh Indonesia, using a qualitative approach, in the form of the Virtual Communication Ethnographic research method. The results of the study generally stated that a negative public opinion was formed from the public towards the summons made by Indonesian Es Teh. The public considered that what was done was inappropriate and unnecessary, this was reflected in the various insults and ridicule that arose as a result of the subpoena. Although on the other hand there is public opinion which states that the criticism made is considered not good because it uses harsh and impolite language or words.